Gradient-index Optics - Charman, W N (Canadian Journal of Optometry, 1982)
The history of man-made devices involving the use of gradients of refractive index is briefly outlined and a typical component, the Wood lens, is described. Current methods for producing controlled gradients are reviewed, together with their limitations and applications. Some possibilities for using gradients to improve the design of spectacle and contact lenses are discussed.